2021
DOI: 10.1161/jaha.120.016890
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term PM 2.5 Exposure and Risks of Ischemic Heart Disease and Stroke Events: Review and Meta‐Analysis

Abstract: Background Fine particulate matter <2.5 µm in diameter (PM 2.5 ) has known effects on cardiovascular morbidity and mortality. However, no study has quantified and compared the risks of incident myocardial infarction, incident stroke, ischemic heart disease (IHD) mortality, and cerebrovascular mortality in relation to long‐term PM 2.5 exposure. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
114
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 178 publications
(127 citation statements)
references
References 124 publications
7
114
5
1
Order By: Relevance
“…Our findings are generally consistent with several previous studies. However, our HR = 1.05 (95% CI: 0.88, 1.25) for 12-month average PM 2.5 and total stroke is lower than a recent meta-estimate (RR = 1.13, 95% CI: 1.11, 1.15) 21 of other studies. Compared with a previous study by Puett et al 28 in the HPFS, we observed generally larger estimates of effect with a longer study period and more cases; however, the results still did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Our findings are generally consistent with several previous studies. However, our HR = 1.05 (95% CI: 0.88, 1.25) for 12-month average PM 2.5 and total stroke is lower than a recent meta-estimate (RR = 1.13, 95% CI: 1.11, 1.15) 21 of other studies. Compared with a previous study by Puett et al 28 in the HPFS, we observed generally larger estimates of effect with a longer study period and more cases; however, the results still did not reach statistical significance.…”
Section: Discussioncontrasting
confidence: 97%
“…Our HR = 1.17 (95% CI: 0.76, 1.81) for PM 2.5 and hemorrhagic stroke is somewhat higher than a recent meta-estimate (RR = 1.10, 95% CI: 1.05, 1.16) 21 ; however, our HR = 0.99 (95% CI: 0.79, 1.25) for PM 2.5 and ischemic stroke is much lower than a recent meta-estimate (RR = 1.18, 95% CI: 1.14, 1.22). 21 …”
Section: Discussioncontrasting
confidence: 87%
“… 1 , 2 Long-term exposure to PM 2·5 is associated with premature mortality from a variety of diseases, including cardiovascular disease, respiratory disease, lung cancer, and lower respiratory infection. 3 , 4 , 5 PM 2·5 is now the leading environmental contributor to the global burden of disease, rising from being the fifth leading contributor among environmental risk factors in 1990, in part driven by declines in household air pollution and unsafe water and sanitation. 1 Recent estimates of PM 2·5 -attributable disease burdens describe global, regional, and national trends, and do not focus on the city scale where 55% of the world's population resides; a figure that is expected to increase.…”
Section: Introductionmentioning
confidence: 99%
“…PM 2.5 is considered more toxic than PM 10 because of its smaller diameter, meaning it can deposit into the alveolar region of the lungs and induce a series of immune responses [2]. Many epidemiological studies reported that exposure to PM 2.5 is associated with adverse health outcomes, such as allergic respiratory diseases, asthma, cardiovascular diseases, neuropsychological diseases, and mortality [3][4][5][6][7]. The major sources of PM 2.5 in Japan include sea salt, biomass combustion, soil dust, and secondary aerosols, which are derived from local emission sources and long-range transportation [8].…”
Section: Introductionmentioning
confidence: 99%